Canadian substance use costs and harms (2015-2017). - Canadian Institute for Substance Use Research; Canadian Centre on Substance Use and Addiction. (Canadian Centre on Substance Use and Addiction, 2020)
This report provides a summary of key findings about the costs and harms of substance use in Canada from 2015 to 2017. Data include the costs of various substances such as alcohol, tobacco, opioids and cannabis. The data are also broken down into four categories: healthcare costs, lost productivity costs, criminal justice costs and other direct costs.
Num Pages: 66 p.